2012
DOI: 10.1002/job.1839
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic evaluation of diversity training outcomes

Abstract: Summary The purpose of this meta‐analysis was to use theory and research on diversity, attitudes, and training to examine potential differential effects on affective‐based, cognitive‐based, and skill‐based outcomes, to examine potential moderators of those effects with a focus on affective‐based outcomes, and finally, to provide quantitative estimates of these posited relationships. Results from 65 studies (N = 8465) revealed sizable effects on affective‐based, cognitive‐based, and skill‐based outcomes as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
216
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(244 citation statements)
references
References 99 publications
6
216
1
8
Order By: Relevance
“…https://doi.org/10.1017/iop.2016.5 police officer behaviors and attitudes toward minorities (Ungerleider & McGregor, 1993). A meta-analysis found that diversity training has positive effects for a variety of outcomes, including those that are cognitive (i.e., learning, knowledge), skills related (i.e., behaviors and behavioral intentions), and attitudinal (Kalinoski et al, 2013).…”
Section: Trainingmentioning
confidence: 99%
“…https://doi.org/10.1017/iop.2016.5 police officer behaviors and attitudes toward minorities (Ungerleider & McGregor, 1993). A meta-analysis found that diversity training has positive effects for a variety of outcomes, including those that are cognitive (i.e., learning, knowledge), skills related (i.e., behaviors and behavioral intentions), and attitudinal (Kalinoski et al, 2013).…”
Section: Trainingmentioning
confidence: 99%
“…There is limited information, to date, available regarding the effectiveness of LGBT awareness training (e.g., Flavin, 1997;Hayes et al, 2004) or LGBTtailored treatment approaches (e.g., Green & Feinstein, 95 2012;Matthews et al, 2014). Initial studies within health contexts have demonstrated positive impacts regarding LGBT staff training (Hardacker et al, 2014;Kalinoski et al, 2013); however, data regarding secondary impacts upon client engagement and clinical outcomes are limited. 100 It is well established in the general clinical and counseling literature, that clients who feel accepted and understood, and are receiving "more culturally sensitive health care" (Lombardi & van Servellen, 2000, p. 295) are more likely to engage with therapy and experience enhanced 105 treatment outcomes (Kelly et al, 2015;Talley, 2013).…”
mentioning
confidence: 99%
“…Given that a small, but meaningful percentage of respondents noted personal, reli-575 gious and/or spiritual views stating that LGBT persons should be 'condemned' or are 'sinful' , this highlights the need for further diversity awareness training (Kalinoski et al, 2013), and/or supervision to explore and address counter transference or other process issues, which may 580 be impacting upon the therapeutic relationship and treatment outcomes (Spector & Pinto, 2011).…”
mentioning
confidence: 99%
“…This has been confirmed by meta-analyses conducted by Z. T. Kalinoski et al (2013), which drew together 96 different empirical studies done on diversity training among a population of almost 8,500 employees. These studies reveal that such practices have a positive influence on the attitudes, behaviours and knowledge of trainees.…”
Section: Diversity Management As An Element Of Hr Practicesmentioning
confidence: 69%